Editorial 14 (2014)
Public policies in education in recent years have advised Colombian educational institutions to focus their efforts on improving quality. With good reason, the results of basic and middle education in the international PISA tests, and the results of higher education in the Shanghai Ranking 2013, require an in-depth analysis. Besides the positivist debate of whether or not social sciences and the humanities in general should be likened to the pure sciences, it’s worth looking in depth at the evaluation model and the National System of Science, Technology and Innovation as a whole. Although the different fields of knowledge respond to different problem areas in the country, the research system greatly privileges engineering, health sciences, agroforestry and the basic sciences, ignoring somewhat the social sciences and humanities (despite the recent implementation of the National Social Science and Humanities Program). Ultimately, it involves revising the place of social sciences and humanities in the Colombian education system, and questioning what is taught and how, in a country where the social fabric is divided by a number of factors: corruption; violence, which increasingly permeates individuals’ lives; and the rapid global changes which alter important sectors such as health and communication, among others. This is the context which teachers and researchers must confront on a day-to-day basis, and with their work think about the country and how to change it. The Santo Tomás University presents here the 14th edition of the journal Quaestiones Disputatae to the scientific community, corresponding to the period January to June 2014, in which the research efforts of academic persons and communities are shown, and through a serious and profound exercise, make a contribution to the construction of a new society. In the first section, relating to social sciences, there are four articles, each relating to a different topic. The first investigates the topic of childhood and analyses the historical conditions that allowed for the emergence of child protection in Colombia and state intervention in the face of child defencelessness. The second article deals with the world of young people and is based on the systematisation of a citizen participation experience in the city of Bogotá. The third study was carried out within the framework of the Clinical and Family Psychology Masters 12 Revista Quaestiones Disputatae - Temas en Debate - Nº 14, 2014 program at the Santo Tomás University, and analyses the systemic and ecological approach of the training of therapists. Finally, the fourth article presents a regional focus, raising the question of whether a Latin American integration is possible. The second section, relating to philosophy, presents an international perspective from Adriano Fabris, especially for Italian readers, in which the philosophical tradition is studied in relation to religious philosophy.Next, there is an article which analyses Dussel’s transmodern utopia as a liberation project. In the third section, dedicated to the field of humanities, there is a study of suicide perceived from the virtue of justice according to St. Thomas and Kant. Then, homage is made to the Boyacense humanist Enrique Medina Flórez, on the first anniversary of his death. From literature, there is an article entitled Identity and otherness based on Sarmiento’s Facundo and Mariátegui’s 7 Essays. In addition, there is an international article by Francisco Antonio Moreno y Escandón and Fr Jacinto Antonio de Buenaventura entitled The Enlightenment vs New Granadine university tradition (1768-1798). In the fifth section, dedicated to theology, there is an international article about the understanding in the continent of the so-called social sin. Additionally, there is the inaugural paper from the university pastoral council conference “Ives Congar” which took place in our university on 16th May 2014. To the efforts of the researchers, those of the institution are also added in order to make Quaestiones Disputatae an internationally visible journal which fulfils the highest quality standards. The academic community can consult the entire catalogue of the journal in the Open Journal System (OJS), and on the institutional website. Collaboration with international databases has begun in order to index the journal. In this manner, the researchers’ articles will reach more readers in different parts of the world. Let this be an opportunity to recognise Dr Alfonso Camargo Fr, who was responsible for the journal during many years, and who, through his important work, gave the journal an academic and humanistic stamp.